Chapter 10. Phonology: Pre-Slavic and Common Slavic Vowels and Diphthongs - Nesset, Tore (Septentrio Educational, 2015)
Now that you have learned about morphology and syntax, you are ready for phonology – the study of sound systems. Phonology is the topic of this and the following three chapters. We start with vowels and diphthongs in the Pre-Slavic and Common Slavic periods. You will learn how the difference between short and long vowels disappeared, and how a number of sound laws created a special type of syllables called “open syllables”. In addition, this chapter gives you the answer to a number of questions about Modern Russian. Why are there no words beginning with the letter ы in Contemporary Standard Russian? Why is ‘city’ represented as град in Leningrad and Stalingrad, but город in Novgorod? Why does the letter н show up in the inflected forms of nouns like имя and время (cf. nominative singular имя vs. genitive singular имени)? Download the video to learn more.